Skills for communicating severe acute respiratory syndrome-coronavirus-2 result to patients and/or relatives - Oladele V. Adeniyi; Dominique K. Kayembe (South African Family Practice)
Clinicians notify positive results of the severe acute respiratory syndrome coronavirus-2 polymerase chain reaction to patients and/or relatives, whilst short message service (SMS) has been adopted as a means of disseminating negative results. Therefore, clinicians should be adequately equipped to provide telephonic consultation whilst delivering a positive test result to patients. The news of the coronavirus disease 2019 (COVID-19) test result often invokes fear of impending death in patients, especially the elderlies and those with comorbidities. In addition, several survivors have reported persistent symptoms and COVID-19-related stigma, which precludes them from immediate re-integration into their workplaces. Consequently, COVID-19 results are perceived as bad news by the members of the public. This article justifies why COVID-19 test results are bad news and also discusses the notification steps to follow when delivering COVID-19 results, whilst also addressing patients’ immediate concerns. The article concludes by highlighting an important safety net for COVID-19 patients and the attending clinician.